A Review on Isolation and Identification of Endophytic Actinobacteria, Their Chemical Structure, Bioactive Compounds, and Potential Medical-Pharmaceutical Applications - Yaser Delbari; Yaser Mohassel; Yadollah Bahrami; Elham Kakaie; Ali Mostafaie (Journal of Mazandaran University of Medical Sciences, 2020)
Over recent years, nosocomial infections, and the morbidity and mortality associated with pathogenic bacteria have dramatically increased due to antibiotic resistance and imposed significant burdens on the global health system. Critical shortage of effective therapeutics against multidrug-resistant bacteria highlights the need for development of novel antibiotics. Actinobacteria are well-known sources of natural bioactive compounds, especially antibiotics. Nearly two-thirds of the antibiotics on the market have actinobacterial origins. Endophytic actinobacteria residing within plants contribute to the plant growth and survival by producing plethora of secondary metabolites. Therefore, isolation, cultivation, and identification of new strains, as well as their potential to produce antimicrobial compounds, are of great importance. Lack of published research in this field highlights the importance of this review in Iran. The aim of this review was to present the latest methods for the isolation and identification of endophytic actinobacteria and introducing relevant databases. We also studied the most recent isolated strains, chemical structure of 51 newly identified secondary metabolites, and their potential medical-pharmaceutical applications. This study revealed that endophytic actinobacteria are prolific sources of bioactive secondary metabolites with high levels of structural diversity and potent pharmaceutical and medicinal applications.